K.M. Takhtarev is one of the First Professional Sociologists in Russia. To the 150th Anniversary of His Birth - A. O. Boronoev (Дискурс, 2021)
Introduction. The article presents the fate and work of the famous Russian sociologist Konstantin Mikhailovich Takhtarev (1871–1925), who would have turned 150 years old in 2021. He was one of the first professional sociologists who played an important role in the institutionalization of Russian sociology. His works and other deeds are still not fully comprehended and, therefore, are insufficiently used in research and in the process of training sociologists. The article presents the main results of his work and the direction of his activities in organizing sociological knowledge in Russia.Methodology and sources. The article implements a historical and biographical approach combined with a comparative analysis of the life and scientific fate of the famous Russian sociologist K. M. Takhtarev, professor of the St Petersburg University (1911–1925). His main works and the results of his activities on the institutionalization of Russian sociology are analyzed.Results and discussion. The name of K.M. Takhtarev stands next to such names as M.M. Kovalevsky, N.I. Kareev, A.S. Lappo-Danilevsky, E.V. de Roberti, P.A. Sorokin, etc. His contribution to the institutionalization of Russian sociology is very significant. He was one of the first to prepare complete textbooks, created his own system of sociology (P. Sorokin), was one of the organizers of the M.M. Kovalevsky Russian Sociological Society, which confirmed the formation of the Russian sociological community. The creation of the country's first sociological institute is associated with his name. N.I. Kareev called him and P.A. Sorokin the first professional sociologists of Russia. The article shows his understanding of the subject of sociology, the basic concepts that reveal the essence of social life, its evolution, through the stages of self-sufficiency – the foundations of his theory. The significance of the systematization of sociological ideas carried out by him, which formed the basis of his system of sociology, is revealed. The role of Takhtarev in the development of genetic sociology as a sociological direction studying the dynamics of forms of society and social institutions is emphasized.Conclusion. The significance of K.M. Takhtarev's ideas for today's sociology is shown and it is argued that it is necessary to refer to his works today. The special relevance of the logic of building his own system of sociology, research experiments in the field of genetic sociology, the substantiation of social laws and the classification of social laws are emphasized.